IMPROVING THE STUDENTS’ SPEAKING ABILITY THROUGH SPEAKING VIDEO PROJECT LEARNING FOR THE SECOND SEMESTER OF INFORMATICS ENGINEERING DEPARTMENT - Diyah Dwi Agustina (Universitas Nahdlatul Ulama Lampung, 2018)
This study is Classroom Action Research that intended to improve the students’ speaking ability and motivation through speaking video project learning for the second semester of Informatics Engineering department UNU Lampung. The participant consisted of 26 students. This study conducted from January-July 2018. This study use Kemmis and Taggart models that is planning, action, observation and reflection of the result. Then, this research employs the triangulation method (observation, interview, and test) for collecting the data. After the data are gathered, they are analyzed and interpreted by using data reduction, categorization and synthesis. The findings were formulated as follow: (1) the students become more active in learning process using the implementation video project learning; (2) the improvement of students’ speaking ability from cycle 1 was 60, cycle 2 was 68, cycle 3 was 78; (3) there is improvement in the students learning motivation.